Analysis of risks factors on organophosphates poisoning on Chinese cabbage farmers in Semangat Village Kecamatan Merdeka Karo Regency - Ambarwati, Nova Florentina; Wiratma, Dicky Yuswardi (Sari Mutiara Indonesia University Press, 2018)
Pesticides of organophosphate type are mostly used on farming because they are easier to resolve in nature, but there was a possibility of high frequency that they were an agent that caused neurological diseases amongst farmers especially in developing countries. The factors influencing the occurrence of pesticide poisonings are internal and external factors, including age, knowledge level, work period as a sprayer, and spraying frequency. The purpose of this research is to analyze the risk factors that cause organophosphate pesticide poisonings on Chinese cabbage farmers in Semangat Village Karo Regency. The methods that are used in this research are with the observational method and cross-sectional approach, with the population of all Chinese cabbage farmers in Semangat Village Karo Regency. The taking of samples uses simple random sampling technique as much as 50 samples, the instruments that are used in this research is using Thermo Indiko for cholinesterase levels inspection and lists of questions for the farmers. The results show that there is no significant correlation between age and organophosphate pesticide poisoning on Chinese cabbage farmers (p > 0,05). Meanwhile, for other factors such as the relation between knowledge, the relation between work period as a sprayer, and the relation between spraying frequency with the level of pesticide poisoning show that there is a significant correlation (p < 0,05). Research results also show that the most dominant variable related to organophosphate pesticide poisoning on Chinese cabbage farmers is spraying frequency (p-value = 0,000 dan odds ratio = 7,707), which means that spraying frequency > 2 times a week has the opportunity of 7,707 bigger risks of organophosphate pesticide poisoning abnormality on Chinese cabbage farmers than with spraying frequency of ≤ 2 times a week